2004
DOI: 10.1242/jeb.01241
|View full text |Cite
|
Sign up to set email alerts
|

Rumen metabolites serve ticks to exploit large mammals

Abstract: SUMMARY Hard ticks spend most of their life isolated from passing vertebrates but require a blood meal to proceed to the next life stage (larva, nymph or adult). These opportunist ectoparasites must be capable of anticipating signals that render suitable hosts apparent. Large ungulates that tolerate a high ectoparasite burden are the favoured hosts of adult hard ticks. Ruminants, comprising the majority of ungulate species, must regularly eruct gases from the foregut to relieve excess pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…It is known that high concentrations of carboxylic acids can act as repellents for the malaria mosquito, Anopheles gambiae, where they can decrease the eYcacy of approaches to mixtures that are otherwise active (Knols et al 1997). Carboxylic acids and oxycarboxylic acids have already been reported as important chemostimuli in the sensory ecology of diVerent haematophagous arthropods such as mosquitoes (Cork and Park 1996;Knols et al 1997), sandXies (Dougherty et al 1999), ticks (Donzé et al 2004) and triatomine bugs (Guerenstein and Guerin 2001). It is quite possible that such acids may also inXuence tsetse Xy behaviour, but the pertinent mixture and doses remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that high concentrations of carboxylic acids can act as repellents for the malaria mosquito, Anopheles gambiae, where they can decrease the eYcacy of approaches to mixtures that are otherwise active (Knols et al 1997). Carboxylic acids and oxycarboxylic acids have already been reported as important chemostimuli in the sensory ecology of diVerent haematophagous arthropods such as mosquitoes (Cork and Park 1996;Knols et al 1997), sandXies (Dougherty et al 1999), ticks (Donzé et al 2004) and triatomine bugs (Guerenstein and Guerin 2001). It is quite possible that such acids may also inXuence tsetse Xy behaviour, but the pertinent mixture and doses remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…As these products formed in the foregut are continually evacuated through eructation, they may provide tsetse Xies with important cues to track ruminants across the range of habitats they have come to occupy in sub-Saharan Africa. Moreover, rumen Xuid odour has already been found to attract other haematophagous arthropods linked to large mammalian herbivores, namely the adult stage of Wve hard tick species that take large blood meals on such hosts (Donzé et al 2004) and the stable Xy Stomoxys calcitrans that is a worldwide pest of livestock (Jeanbourquin and Guerin 2007). Considering the success of tsetse Xies in exploiting herbivore mammals, especially ruminants, we hypothesised that volatiles from the rumen might serve as a source of chemostimuli for tsetse species of diVerent subgenera.…”
Section: Introductionmentioning
confidence: 99%
“…Breath contains various cues such as moisture and heat in addition to volatile compounds such as CO 2 , acetone, ammonia, and H 2 S and behavioural responses to these compounds are presented in Table 3. In ruminants, numerous compounds that are by-products of rumen digestion, such as 1-octen-3-ol, also induce behavioural responses (Donzé et al 2004). …”
Section: Breathmentioning
confidence: 99%
“…Ruminants regularly eruct gases from the foregut to relieve pressure and Donzé et al (2004) reported attraction in the laboratory of adult A . variegatum, A. hebraeum, I.…”
Section: Ruminant By-productsmentioning
confidence: 99%
“…103 and in cardiovascular disease in which the levels of 3-nitrotyrosine (3.22) were found to be increased. 104 Because natural nitrated metabolites are relatively rare in nature their nitration mechanisms have been the subject of several studies and are believed to be limited to two mechanisms, direct nitration with reactive nitrogen species (NO) and oxygenation of amines by specialised oxigenases.…”
Section: Cytotoxicitymentioning
confidence: 99%